ANALISA PARAMETER HIDROGRAF SATUAN SINTETIK METODE NASH DAN SOIL CONSERVATION SERVICE (SCS) - Puji Harsanto; Reza Afrah Afifah; Bayu Krisna Wisnulingga; Burhan Barid (Racic : Rab Construction Research, 2023)
Water construction developments are increasing over time with the aim of preventing floods, raising water levels, and helping water resource management. However, in the planning process, debit data for 20 years is very difficult to obtain. Therefore, there is a Synthetic Unit Hydrograph (SUH) method to help analyze without using rainfall data and only using watershed characteristics for hydrological analysis. In this study, we will analyze the synthetic unit hydrograph parameters using the Nash and Soil Conservation Service (SCS) methods and compare them with data from the Gemawang AWLR in the Code River sub-watershed. A comparison was made to find out which method is suitable for the Code River sub-watershed at the AWLR Gemawang station. The suitability index or RÂ² of the two methods shows results that are close to one or very related. The regression angle of the variation SCS method obtained an angle of 38Ëš, at the time of rising 36.5Ëš and at recession time of 38.6Ëš. The Nash variation method gets 40.1Ëš for one hydrograph data, 40.6Ëš for rising time and 43.3Ëš for descending time.